Special Aspects in Pediatric Surgical Inpatient Care of Refugee Children: A Comparative Cohort Study - Nina K. Friedl; Oliver J. Muensterer (MDPI AG, 2019)
Background: Recently, the number of refugees in Germany has skyrocketed, leading to a marked increase in refugee children admitted to hospitals. This study describes the special characteristics encountered in pediatric surgical inpatient refugees compared to locally residing patients. Methods: Hospital records of minor refugees admitted to our department from 2005 up to and including 2015 were retrospectively reviewed. Demographic data, diagnoses, comorbidities, body mass indexes, hemoglobin values, and lengths of stay were extracted and statistically compared to local patients. Results: A total of 63 refugee children were analyzed and compared to 24,983 locally residing children. There was no difference in median body mass index (16.2 vs. 16.3, respectively, p = 0.26). However, refugee children had significantly lower hemoglobin values (11.95 vs. 12.79 g/dL, p < 0.0001) and were more likely to be colonized with methicillin-resistant Staphylococcus. aureus (8% vs. 0.04%, p < 0.01). Refugees were much more likely to present with burn injuries (16% versus 3% of admissions, p < 0.001), esophageal foreign bodies (4% vs. 0.5%, p < 0.001), as well as trauma, except for closed head injury. Conclusion: The cohort of refugee children in this study was found to be at a particular risk for suffering from burn injuries, trauma, foreign body aspirations, and anemia. Appropriate preventive measures and screening programs should be implemented accordingly.